2017
DOI: 10.1245/s10434-017-5860-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of 18F-FDG PET/CT for Axillary Lymph Node Metastasis in Invasive Ductal Breast Cancer

Abstract: Combining the pSUV of each molecular subtype with the nodal F-FDG uptake finding can improve the prediction of ALN metastasis in IDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…However, despite the very high specificities (99.0% and 99.5%) of FDG-PET/CT observed in this study, the sensitivities of the human diagnosis with FDG-PET/CT for axillary LN metastasis were quite poor (59.8% and 57.4%). Similar results have been reported by other groups [3][4][5][6][7][8][9]. To improve the sensitivity, we constructed an AI-assisted diagnosis system.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, despite the very high specificities (99.0% and 99.5%) of FDG-PET/CT observed in this study, the sensitivities of the human diagnosis with FDG-PET/CT for axillary LN metastasis were quite poor (59.8% and 57.4%). Similar results have been reported by other groups [3][4][5][6][7][8][9]. To improve the sensitivity, we constructed an AI-assisted diagnosis system.…”
Section: Discussionsupporting
confidence: 71%
“…The 'gold standard' for diagnosing axillary LN involvement is a pathological examination of aspiration cytology, a sentinel LN biopsy (SLNB), and an axillary LN dissection (ALND); however, these are invasive methods. In contrast, the utility of noninvasive 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) for the diagnosis of axillary LN metastasis in patients with breast cancer has been described by several research groups [3][4][5][6][7][8][9], one of which achieved a relatively low pooled sensitivity value of 60% and a quite high pooled specificity value of 97% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that the combination of lymph node CT indicators and tumor TLG values can improve the accuracy of PET/CT for the diagnosis of lymphatic metastasis in patients with cervical cancer [33]. Similar combined methods are also applied to breast cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, the ratio of the ALN to the primary tumor SUVmax was used. In a study by Song et al [13], although they established a predictive model for ALN metastasis using the cutoff SUVmax adjusted for the molecular subtypes, subtype-specific predictive values were not included.…”
Section: Discussionmentioning
confidence: 99%
“…We did not analyze the SUVmax of the ALNs. Some investigators [13,[23][24][25]. However, in this study, we tried to focus on the direct association between the tumor SUVmax and ALN status because there is no reliable threshold for SUVmax LN to discriminate benign from malignant lymph nodes presently [26].…”
Section: Discussionmentioning
confidence: 99%